GAMBARAN PENGELOLAAN KELAS OLEH GURU PAUD SE-KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Puspitasari, Enda Puspitasari; ', Sutanti; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: the aimed of this study to determine the class management by early childhood teachers throughout Payung Sekaki District of Pekanbaru. Population and sample in this research amount to 21 people S1 early childhood teachers in Sub District of Payung Sekaki Pekanbaru. The data collection techniques that use a questionnaire. Data analysis technique using a percentage formula. The results were obtained by early childhood teachers classroom management throughout Payung Sekaki District of Pekanbaru overall gain a percentage of 89.74% which is in the category